2021
DOI: 10.21203/rs.3.rs-199162/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fecal Sample Collection Methods and Time of Day Impact Microbiome Composition and Short Chain Fatty Acid Concentrations

Abstract: Associations between the human gut microbiome and health outcomes continues to be of great interest, although fecal sample collection methods which impact microbiome studies are sometimes neglected. Here, we expand on previous work in sample optimization, to promote high quality microbiome data. To compare fecal sample collection methods, amplicons from the bacterial 16S rRNA gene (V4) and fungal (ITS2) region, as well as short chain fatty acid (SCFA) concentrations were determined in fecal material over three… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…This was largely prevented by the use of the Omnigene gut and the Zymo research DNA stabilization systems. Both stabilization methods, RT-ZB and RT-OB, resulted in microbiome profiles with lower proportions of Actinobacteria, a finding that has been reported before in studies comparing the Omnigene Gut to other collection methods [14,37,39]. Considering the fact that this decrease in Actinobacteria is not observed in the samples stored at RT without buffer, this is most likely to be an effect of storage in stabilization buffer.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This was largely prevented by the use of the Omnigene gut and the Zymo research DNA stabilization systems. Both stabilization methods, RT-ZB and RT-OB, resulted in microbiome profiles with lower proportions of Actinobacteria, a finding that has been reported before in studies comparing the Omnigene Gut to other collection methods [14,37,39]. Considering the fact that this decrease in Actinobacteria is not observed in the samples stored at RT without buffer, this is most likely to be an effect of storage in stabilization buffer.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, alternative sampling methods are essential to facilitate large population level microbiome studies from broad geographic locations. To this end, several approaches have been tested aiming to stabilize the microbial composition in faecal samples during transportation at ambient temperature, such as the Omnigene gut system, the Stratec stool collection tube, or the Stool Nucleic Acid Collection and Preservation Tube [13][14][15]. Furthermore, after sampling, extraction of nucleic acids is shown to be potentially the most critical step affecting the outcome of microbiome studies.…”
Section: Introductionmentioning
confidence: 99%
“…How such factors affect the fecal consistency should be further studied. Moreover, there are challenges with stool collections due to heterogenicity in the material (32). We used EasySampler collection kit and participants were advised to collect small samples from the defection in 2 tubes from the same bowel movement.…”
Section: Discussionmentioning
confidence: 99%
“…For example, reads generated by the V4 primer pair showed a higher alpha diversity of the gut microbial community than V1-V2 and V3-V4 79 . In addition, a recent study showed significant differences in bacterial composition that result from collecting stool samples using different stool collection methods compared to immediate freezing 80 . This may have a negative impact on statistical power.…”
Section: 06e-02mentioning
confidence: 99%